A characterization of the antimalarial activity of the bark of Cylicodiscus gabunensis Harms. (23rd February 2017) - Aldulaimi, Omar; Uche, Fidelia I.; Hameed, Hamza; Mbye, Haddijatou; Ullah, Imran; Drijfhout, Falko; Claridge, Timothy D.W.; Horrocks, Paul; Li, Wen-Wu
Abstract: Ethnopharmacological relevance and aim: A decoction of the bark of Cylicodiscus gabunensis Harms is used as a traditional medicine in the treatment of malaria in Nigeria. This study aims to validate the antimalarial potency of this decoction in vitro against Plasmodium falciparum and define potential bioactive constituents within the C. gabunensis bark. Materials and methods: A bioassay-guided separation and fractionation protocol was applied to C. gabunensis extracts, exploiting the use of a Malaria Sybr Green I Fluorescence assay method to monitor antiproliferative effects on parasites as well as define 50% inhibition concentrations. Spectroscopic techniques, including GC-MS, TOF LC-MS and 1 H NMR were used to identify phytochemicals present in bioactive fractions. Analogues of gallic acid were synthesized de novo to support the demonstration of the antimalarial action of phenolic acids identified in C. gabunensis bark. In vitro cytotoxicity of plant extracts, fractions and gallate analogues was evaluated against the HepG2 cell line. Results: The antimalarial activity of ethanolic extracts of C. gabunensis bark was confirmed in vitro, with evidence for phenolic acids, primarily gallic acid and close analogues such as ethyl gallate, likely providing this effect. Further fractionation produced the most potent fraction with a 50% inhibitory concentration of 4.7 µg/ml. Spectroscopic analysis, including 1 H NMR, LC-MS and GC-MS analysis of this fraction and its acid hydrolyzed products, indicated the presence of conjugates of gallic acid with oligosaccharides. The extracts/fractions and synthetic alkyl and alkenyl gallates showed moderate selectivity against P. falciparum . Conclusions: These results support the use of the bark of C. gabunensis as a traditional medicine in the treatment of human malaria, with phenolic acid oligosaccharide complexes evident in the most bioactive fractions. Graphical abstract: